2019
DOI: 10.2141/jpsa.0180081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hogweed (<i>Heracleum persicum</i>) Powder, Flavophospholipol, and Probiotics as Feed Supplements on the Performance, Carcass and Blood Characteristics, Intestinal Microflora, and Immune Response in Broilers

Abstract: The effect of different levels of hogweed powder (HP; Heracleum persicum), flavophospholipol (antibiotic), and probiotics in diet on the performance, carcass quality, blood biochemical parameters, immunity, and intestinal flora of broiler chickens was investigated. In total, 270-day-old male broilers were randomly assigned to six treatment groups as follows: control basal-diet and diet supplemented with flavophospholipol, probiotics, or 0.25, 0.5, and 0.75% HP. Birds in each group were divided into three subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…On the other hand, it was reported that probiotics had no significant impact on feeding frequency, feeding duration, preening, resting, fighting, and feather pecking behaviors, compared to the control group (45). Moreover, some previous results indicated no improvement in feed intake in probioticsupplemented chicks (46). These negative results might be partially due to different probiotic products or the doses used in the diet formulation.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, it was reported that probiotics had no significant impact on feeding frequency, feeding duration, preening, resting, fighting, and feather pecking behaviors, compared to the control group (45). Moreover, some previous results indicated no improvement in feed intake in probioticsupplemented chicks (46). These negative results might be partially due to different probiotic products or the doses used in the diet formulation.…”
Section: Discussionmentioning
confidence: 92%
“…The administering of probiotics can be included in the basal diet or combined with raw materials that contain prebiotics to enhance its effect 20 , 30 , 50 – 54 , 67 . The probiotic can be given alone or with another additive without any negative effect such as acidifiers and phytogenics 25 , 26 , 32 , 42 , 44 . Furthermore, probiotics can contain one or multiple microorganism strains that can be added to animals' diets 24 , 28 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The administering of probiotics can be included in the basal diet or combined with raw materials that contain prebiotics to enhance its effect 20,30,[50][51][52][53][54]67 . The probiotic can be given alone or with another additive without any negative effect such as acidifiers and phytogenics 25,26,32,42,44 . Furthermore, probiotics can contain one or multiple microorganism strains that can be added to animals' diets 24,28,37 .…”
Section: Discussionmentioning
confidence: 99%